2005
DOI: 10.1016/j.catcom.2005.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of SO42- on the catalytic combustion of soot using O2 and NO/O2 mixtures over Na-promoted Al2O3 catalysts

Abstract: Publication information Catalysis Communications, 6 (7): 472-475Publisher Elsevier Item record/more information

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The NO+O 2 mixture has two roles in the soot removal mechanism, in agreement with other authors for DPF materials. , On one hand, it can react with soot as the gas–solid reaction that has been described above with activation energy values around 100 kJ mol –1 , which, for this material, was superimposed with other processes and cannot be adjusted. On the other hand, NO can be oxidized to NO 2 and adsorbed as nitrites or nitrates, , which lately react with soot being more reactive than gas-phase NO 2 . The profile of NO (Figure S2) also confirmed NO consumption at temperatures higher than 600 K to form nitrate species, which is the characteristic that makes this Pt–Ba–K/Al 2 O 3 an effective catalyst for NSR technology.…”
Section: Resultsmentioning
confidence: 99%
“…The NO+O 2 mixture has two roles in the soot removal mechanism, in agreement with other authors for DPF materials. , On one hand, it can react with soot as the gas–solid reaction that has been described above with activation energy values around 100 kJ mol –1 , which, for this material, was superimposed with other processes and cannot be adjusted. On the other hand, NO can be oxidized to NO 2 and adsorbed as nitrites or nitrates, , which lately react with soot being more reactive than gas-phase NO 2 . The profile of NO (Figure S2) also confirmed NO consumption at temperatures higher than 600 K to form nitrate species, which is the characteristic that makes this Pt–Ba–K/Al 2 O 3 an effective catalyst for NSR technology.…”
Section: Resultsmentioning
confidence: 99%
“…In the latter case NO, present in the exhaust gas (in combination with a suitable NO oxidation catalyst), promotes soot combustion through the formation of NO 2 which then reacts with C (s) transferring an O atom and regenerating NO [16][17] Since the oxidation of NO is a primary step both in the trapping onto an NSR material and the promotion of soot combustion on a DPF, the attempt to combine both of these technologies into a single catalytic bed seems obvious. Furthermore, it has been reported that the presence of a NSR system improves particulate removal from diesel exhausts [1,[18][19][20].…”
mentioning
confidence: 99%
“…The importance of the interaction between surface nitrates and soot and the beneficial effect on the soot oxidation process is also documented by Sullivan et al [98] suggesting that on the Na/Al 2 O 3 catalyst NO adsorbs in the form of nitrites/nitrates, which can further decompose, i.e., releasing NO 2 . Shuang et al [99] indicated the NO 2 derived from nitrates decomposition on Pt-Mg/Al 2 O 3 catalysts as beneficial for the soot oxidation activity.…”
Section: Dpnr Catalysts For the Simultaneous Removal Of No X And Sootmentioning
confidence: 68%